Comparison of Conventional and Online Transportation in Batam - Rizqi Valiant; Indrastuti Indrastuti (LEADER: Civil Engineering and Architecture Journal, 2023)
The existence of online transportation modes has attracted the attention of many consumers. This condition often triggers conflicts between conventional transportation drivers and online transportation drivers. This paper focuses on the performance between the two modes of transportation, finding out the advantages and disadvantages of online and conventional transportation. Data analysis uses the SPSS (Statistical Package for the Social Sciences) method. The questioner will collect 100 respondents to find out the results of comparing online and conventional transportation in Batam. The results obtained from the respondents' responses are pretty satisfied with online transportation, and this transportation outperforms conventional transportation in terms of service, price, comfort, safety, and practicality.